An interstitial deletion of chromosome 7(q35). Issue 9 (September 1994) - Fagan, K; Kennedy, C; Roddick, L; Colley, A
Abstract : We describe a patient with developmental delay, mild dysmorphic features, and monosomy of 7q35. Only one other patient with an interstitial deletion of this band has been previously reported. A review of clinical features of these two children did not show similarities in dysmorphic features. Reports of patients with other 7q interstitial deletions are listed.